Erógena. - Arriola, Magali; Max, Roberto; Sánchez, Osvaldo; Exhibition. Erógena (1). Exhibition. Erógena (2). Museo de Arte Carrillo Gil Mexico. SMAK (Stedelijk Museum voor Actuele Kunst) Gent. Instituto Nacional de Bellas Artes Mexico. SMAK (Stedelijk Museum voor Actuele Kunst) Gent. 2000-03-15. 2001-09-23. 2000-06-11. 2001-11-19 (Gent Mexico : Museo de Arte Carrillo Gil Mexico SMAK (Stedelijk Museum voor Actuele Kunst) Gent, 2000)
Abaroa, Eduardo ; Aldana, Rodrigo ; Arce, Marco ; Arias, Carlos ; Artemio ; Brunet, Fernanda ; Calderon, Miguel ; Edeza, Ivan ; Eibenschutz, Galia ; Garza, Javier de la ; Galan, Julio ; Glassford, Thomas ; Gomulicki, Maurycy ; Lichis, Los ; Molina, Gabriela ; Monsivais, Gerardo ; Moszka, Richard ; Orlaineta, Edgar ; Rios, Angel Ricardo Ricardo ; Rossell, Daniela ; SEMEFO ; Slim, Pedro ; Toledo, Francisco
biog. p. 92-93
l
Engels
Spaans
boek